MICROSITE S.id SEBAGAI JEMBATAN PEMBELAJARAN IPAS TENTANG SEJARAH DAN BUDAYA INDONESIA UNTUK KELAS III SEKOLAH DASAR - Situmorang, Raja Uruk; Suciptaningsih, Oktaviani Adhi; Pristiani, Riska (STKIP Persada Khatulistiwa Sintang, 2025)
The utilization of digital technology in elementary education is increasingly necessary to address the challenges of conventional learning methods, which may not be engaging enough for students. This study aims to develop the microsite s.id as a learning media for IPAS (Social Sciences and Natural Sciences) with a focus on the history and culture of Indonesia for third-grade elementary school students. The development model used is an adaptation of Richey and Klein’s framework, which includes the stages of analysis, design, development, and evaluation. The product was validated by two validators, an expert in content and an expert in media, with validation percentages of 87% and 91%, respectively, classified as